Alleviating grazing damage by white-fronted geese: an optimal foraging approach - Amano, T; Ushiyama, K; Fujita, G; Higuchi, H (Journal of Applied Ecology, 2004)
1. Agricultural damage by wildlife is a serious constraint on the coexistence of humans and wildlife. Understanding the behavioural processes involved in such agricultural damage will inform management actions. In this study, a linear programming model based on optimal foraging theory was used to formulate management strategies designed to reduce wheat damage caused by white-fronted geese Anser albifrons around Lake Miyajimanuma in Japan.2. Geese feed on rice grains or wheat leaves. Their choice of food is constrained by their daily energy requirement, daily nitrogen requirement, digestive capacity and daily maximum foraging time. With these constraints, we predicted the proportion of geese that should forage on wheat leaves under energy-maximizing, nitrogen-maximizing and time-minimizing strategies, and compared the results with the observed proportion.3. Our predictions for the energy-maximizing strategy successfully explained the variation in the observed proportion of geese foraging on wheat leaves. It appeared that nitrogen constraints drove the geese to forage on wheat in autumn, but energy considerations drove the geese to forage on wheat plus rice in late spring.4. Based on these results, we predicted that by increasing the harvest remains of rice by 30%, a large reduction in wheat damage could be achieved both in autumn and in spring. Damage could be reduced further by supplying protein-rich food, such as grass on fallow fields and on ridges of rice fields in autumn, and by leaving geese foraging in rice fields undisturbed.5. Synthesis and applications. Optimal foraging models that consider foraging goals and constraints have considerable potential for identifying measures for minimizing agricultural damage problems caused by grazing bird species. Specifically, for geese grazing on wheat fields in Japan, we advocate increasing the availability of alternative protein-rich foods, such as rice harvest remains and grass, and minimizing disturbance to geese foraging on rice fields.